Efektifitas endorphin massage terhadap fungsi seksual perempuan pada masa menopause - Sri Wahyuni; Tutik Rahayu (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
Abstract: The purpose of this study is to identify the effectiveness ofendorphine massage on female sexual function during menopause inNgampel District of Kendal Regency. Sampling was done by samplingcriteria acsidental aged less than 60 years old, have a husband, in a healthycondition. Data processing was performed using the Wilcoxon test todetermine differences in sexual function before and after the interventionwhile endorphine effectiveness of massage performed by using MannWhitney.Hasil research: Wilcoxon test showed that there are significantdifferences in sexual function before and after being given endorphineMassage with p value 0.00. While Mann Whitney test showed p value of0.13 and the value of z score of -2.828, which means there is a stronginfluence among endorphine Massage to increased sexual function soendorphine Massage is effective for improving sexual function.